Job strain and the risk of inflammatory bowel diseases: individual-participant meta-analysis of 95,000 men and women. - Katriina Heikkilä; Ida E H Madsen; Solja T Nyberg; Eleonor I Fransson; Kirsi Ahola; Lars Alfredsson; Jakob B Bjorner; Marianne Borritz; Hermann Burr; Nico Dragano; Jane E Ferrie; Anders Knutsson; et al. (PLoS ONE)
Background and aims Many clinicians, patients and patient advocacy groups believe stress to have a causal role in inflammatory bowel diseases, such as Crohn's disease and ulcerative colitis. However, this is not corroborated by clear epidemiological research evidence. We investigated the association between work-related stress and incident Crohn's disease and ulcerative colitis using individual-level data from 95,000 European adults. Methods We conducted individual-participant data meta-analyses in a set of pooled data from 11 prospective European studies. All studies are a part of the IPD-Work Consortium. Work-related psychosocial stress was operationalised as job strain (a combination of high demands and low control at work) and was self-reported at baseline. Crohn's disease and ulcerative colitis were ascertained from national hospitalisation and drug reimbursement registers. The associations between job strain and inflammatory bowel disease outcomes were modelled using Cox proportional hazards regression. The study-specific results were combined in random effects meta-analyses. Results Of the 95,379 participants who were free of inflammatory bowel disease at baseline, 111 men and women developed Crohn's disease and 414 developed ulcerative colitis during follow-up. Job strain at baseline was not associated with incident Crohn's disease (multivariable-adjusted random effects hazard ratio: 0.83, 95% confidence interval: 0.48, 1.43) or ulcerative colitis (hazard ratio: 1.06, 95% CI: 0.76, 1.48). There was negligible heterogeneity among the study-specific associations. Conclusions Our findings suggest that job strain, an indicator of work-related stress, is not a major risk factor for Crohn's disease or ulcerative colitis.